Experimental studies on T-stub to hollow section column connection bolted by T-head square-neck one-side bolts under tension. (March 2021) - Wang, Peijun; Sun, Lele; Zhang, Boxun; Yang, Xiaoxia; Liu, Fangzhou; Han, Zhenlin
Abstract: A novel T-head Square-neck One-side Bolt (TSOB) was proposed and tensile tests on the T-head Square-neck One-side Bolts bolted Connection (TSOBC) for T-stub to Hollow Square Steel Tube (HSST) were conducted. In total, six TSOBCs and three Standard High-strength Bolts bolted Connections (SHBCs) were tested. Four failure modes were found in the test, namely, (1) column wall yielding, (2) column wall yielding with bolt hole shearing, (3) T-stub flange yielding, and (4) bolt failure. Compared to the SHBC, the tensile yield strength and tensile ultimate strength of TSOBCs with vertical and horizontal slotted bolt holes both decreased if the connections encountered the column wall yielding, the column wall yielding with bolt hole shearing, or the T-stub flange yielding failure. The Gomes and Yeomans models were modified to calculate the bending yield strength of the column wall of TSOBC under the failure mode of column wall yielding with bolt hole shearing. The modified Gomes model was recommended to design TSOBC failed by column wall yielding with bolt hole shearing. Theoretical models for calculating the bending yield strength of T-stub flange with slotted bolt holes of TSOBC was also presented, and calculated values were in good agreement with test results. Graphical abstract: Image 1 Highlights: A novel T-shaped One-side Bolts bolted Connection (TOBC) was presented. Tests on TOBC of T-stub to Hollow Section Steel Tube (HSST) under tension were conducted. Gomes model and Yeomans model were modified for application in TOBC. Design methods for calculating tensile yield strength of TOBC were proposed.